Nakum – Ciudad Maya, Petén, Guatemala - Quintana, Oscar (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The Maya City of Nakum, is after Tikal, the urban centre with exposed architecture in the Northeast of Petén, Guatemala, that has been most frequently investigated. From 1994 until 2006 the Institute for Anthropology and History of Guatemala realized the project: “Cultural Triangle- Yaxhá, Nakum, Naranjo”, with the support of the Government of Germany through the Commission of Archaeology of Non-European Cultures (KAAK) of the German Archaeological Institute (DAI) and the German Reconstruction Credit Institute (KfW). In this document we present the results of the study and conservation works of architecture and urban landscape in the southern sector of the city. Special emphasis is placed on the elevated sector of the palace with 16 courtyards and 44 constructions. We compare the results of the study with those available for the palaces in Tikal, La Blanca and San Clemente.The article will be available as a PDF in the near future.